Metaphor Analysis in “Death By A Thousand Cuts” and “False God” Song Lyrics by Taylor Swift - Olivia Apriliani Muslimah; Afni Apriliyanti Devita (Fakultas Ilmu Budaya and LPPM Universitas Sebelas April, 2023)
Taylor Swift is an American singer who released the album Lover in 2019. In the album, there are songs titled